Preventing black triangles around posterior maxillary implants using customized peek healing abutments: A case report - Raisa Oktaviani Yanto Putri; Vinni Nichianishi; Vita Mulya Passa Novianti; Setyawan Bonifacius (Indonesian Journal of Prosthodontic, 2026)
Background: Posterior maxillary implant placement is often challenging due to low bone density, limited soft tissue support, and a higher risk of black triangle formation. Prefabricated healing abutments are manufactured in standard shapes and often fail to guide soft tissue maturation according to individual anatomy. In contrast, custom healing abutments allow precise shaping of the emergence profile and supporting better peri-implant tissue healing. Case: A 31-year-old female presented with a missing upper left second premolar and masticatory discomfort. Clinical and radiographic examinations confirmed adequate bone volume for implant placement. Management: An implant (Dentis Implant s-Clean SQ, 4.0 × 10 mm) was placed using a digitally designed and 3D-printed surgical guide. A custom Polyetheretherketone (PEEK) healing abutment was fabricated and adjusted using flowable composite to mimic the natural gingival contour. This approach minimized repeated abutment disconnection and facilitated soft tissue maturation. After three months, an open-tray impression was made, and a screw-retained zirconia crown was delivered. Conclusion: Custom PEEK healing abutments demonstrate superior adaptation to peri-implant soft tissues, preserve gingival architecture, and effectively prevent black triangle formation compared to prefabricated abutments. Their use is recommended in posterior maxillary implant restorations to enhance functional and biological outcomes. Keywords: black triangle; customized healing abutment; dental implant; PEEK (polyetheretherketone)